A NOVEL DESIGN OF 17.5 KV HV FEEDTHROUGH FOR ARJUNA 2.0 - Saefurrochman Saefurrochman; Darsono Darsono; Suhadah Rabi’atul Adabiah; Elin Nuraini; Sutadi Sutadi; Tanti Ardiyati (Website, 2021)
A NOVEL DESIGN OF 17.5 KV HV FEEDTHROUGH FOR ARJUNA 2.0. A novel design of the 17.5 kV feedthrough for Arjuna 2.0 Cockcroft Walton generator has been proposed. It is used for connecting the output of RF transformer oscillator (in the outside of horizontal vessel) with the input of voltage multiplier (inside of horizontal vessel) of the Cockcroft Walton generator. It was equipped by covers on left and right side. The designed feedthrough was simple, compact, easy to manufacture, high performance to prevent flashover and also it was applied to Arjuna 2.0 Cockcroft Walton. It was made from teflon (PTFE) and solid copper, which have high dielectric strength, capable of withstanding press loads, and easy to manufacture. The shortest distance between grounding with conductor radially was 43.25 mm, and 253.5 mm for feedthrough surface. The design was verified by Finite Element Method software and continued with performance testing. According to simulation, the stress of voltage is high about 16 kV to 17.5 kV on feedthrough conductor and 0 to 3 kV on feedthrough flange. The electric field of the covered feedthrough is lower than the coverless feedthrough. The highest and lowest electric fields are 1.26 x 106 V/m and 1 x 105 to 2 x 105 V/m respectively. Furthermore, feedthrough has been tested up to 120 kV and no discharge occurred. It means this design can be operated for 17.5 kV and it was successful installed on Arjuna 2.0 Cockcroft Walton generator.